Workaholism in organizations : work and health consequences - Burke, Ronald J. (Journal of organizational change management, 2004)
Organizational change initiatives are successful only through the efforts of the people, so it is important to look beyond surface reactions and understand the deeper implications of employees' visible work habits. By integrating work from several disciplines, this paper poses a series of questions aimed at creating better awareness of differences in how and why people work. Historic tracking of beliefs about work in the USA is provided as an example of how a positive foundation of strong work ethic can become the dysfunctional extreme of workaholism.